Heavy metal contamination in soils of greenhouse vegetable production systems in a cold region of China - Lv, Pin; Wei, Zimin; Yu, Zhimin; Zhang, Jizhou; Wang, Limin (International Journal of Agricultural and Biological Engineering, 2019)
Heavy metal (HM) contamination in soils of greenhouse vegetable production (GVP) systems has drawn increasing attention in terms of food safety. In the present study, 64 surface soils were sampled, and the concentrations of select HMs were determined using atomic absorption spectroscopy. The results showed that the concentrations of cadmium (Cd), lead (Pb), zinc (Zn), copper (Cu), nickel (Ni) and chromium (Cr) in the soils were (0.2±0.2) mg/kg, (26.5±8.4) mg/kg, (101.4±43.2) mg/kg, (29.1±8.6) mg/kg, (24.5±3.3) mg/kg, and (56.5±6.3) mg/kg, and the corresponding accumulation index (AI) values were 2.30, 1.10, 1.43, 1.45, 1.07, and 0.97, respectively. The spatial distribution of the HMs suggested that Cd pollution displays a fractionation effect, which may be related to the source of Cd and its mobility. The concentration of Zn was significantly correlated with that of other HMs, implying that a comprehensive interactive effect might occur between Zn and other HMs. Furthermore, the values of the potential ecological risk index (RI) ranged from 41.23 to 185.91, meaning that attention should be paid to HM contamination of GVP soils to ensure food quality and safety.Keywords: heavy metal contamination, cold region, greenhouse vegetable production (GVP), distribution, ecological risk, food quality, food safetyDOI: 10.25165/j.ijabe.20191202.4306Citation: Lv P, Wei Z M, Yu Z M, Zhang J Z, Wang L M. Heavy metal contamination in soils of greenhouse vegetable production systems in a cold region of China. Int J Agric & Biol Eng, 2019; 12(2): 98–102.